INDONESIAN AMBASSADOR FULL OF PRAISES FOR USM INTERNATIONALISATION PROGRAMME - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 16 October 2015 – Universiti Sains Malaysia (USM) is regarded to be among the best research universities in the country, as well as in having a truly progressive and well-planned internationalisation programme.